De Novo Anti-HLA DSA Characteristics and Subclinical Antibody-Mediated Kidney Allograft Injury. Issue 10 (October 2016) - Yamamoto, Takayuki; Watarai, Yoshihiko; Takeda, Asami; Tsujita, Makoto; Hiramitsu, Takahisa; Goto, Norihiko; Narumi, Shunji; Katayama, Akio; Morozumi, Kunio; Uchida, Kazuharu; Kobayashi, Takaaki
Abstract : Background: It is unclear whether all donor-specific antibodies (DSA) can cause chronic antibody-mediated rejection (AMR). Subclinical stage before manifestation of renal dysfunction may be a critical period for reversing AMR. The aim of our study was to identify factors related to the development of subclinical AMR and to clarify the characteristics of de novo DSA. Methods: Eight hundred ninety-nine renal transplants were screened for HLA antibody. De novo DSA were detected in 95 patients. Forty-three patients without renal dysfunction who underwent renal biopsies were enrolled in this study. Eighteen patients (41.9%) were diagnosed with biopsy-proven subclinical AMR and treated with plasmapheresis and rituximab-based therapy, whereas 25 showed no findings of AMR. Results: Significant subclinical AMR-related factors were younger recipients, history of acute T cell–mediated rejection and DSA class II, especially DR-associated DSA. Mean fluorescence intensity (MFI) values of DR-DSA were significantly higher, whereas DQ-DSA was not different between subclinical AMR and no AMR. The ΔMFI (>50%), DSA-MFI values greater than 3000, and C1q binding DSA were also significant subclinical AMR-related factors ( P < 0.05). Among 18 patients treated for subclinical AMR, 8 patients (44.4%) obtained over 50% reduction of DSA-MFI and/or improvement or no deterioration of pathological findings. In contrast, 25 patients without subclinical AMR did not show renal dysfunction clinically. Moreover, all of the 8 patients with rebiopsy after 2 years continued to demonstrate no AMR. Conclusions: About 40% of patients with de novo DSA demonstrated biopsy-proven subclinical AMR, leading to progressive graft injury. To validate the intervention and treatment for de novo DSA-positive patients without renal dysfunction, further study is necessary. Abstract : The authors describe a population of kidney transplant recipients with de novo DSA, no deterioration of renal function, and a concomitant kidney biopsy. They report on the factors associated with the occurrence of subclinical antibody-mediated rejection. Supplemental digital content is available in the text.